Counterion condensation or lack of solvation? Understanding the activity of ions in thin film block copolymer electrolytes. Issue 31 (16th June 2020) - Lei, Qi; Li, Ke; Bhattacharya, Deepra; Xiao, Jingya; Kole, Subarna; Zhang, Qingteng; Strzalka, Joseph; Lawrence, Jimmy; Kumar, Revati; Arges, Christopher G.
Abstract : Dissociation of ion charge pairs in block copolymer electrolytes and its relation to activity coefficients and normalized ionic conductivity. Abstract : Polymer electrolytes are found at the heart of numerous electrochemical technologies involved in energy storage, conversion and separations. An important property of these materials is their partitioning behavior of ions in aqueous solutions and its effect on the activity of the ions within the polymer electrolyte. In this work, the fraction of condensed counterions ( f c ) were quantified in nanostructured block copolymer electrolyte (BCE) thin films with new and established experimental techniques. The transition between the osmotic-controlled regime and condensation-controlled regime in BCEs was identified using environmental GI-SAXS and solution uptake measurements via a quartz crystal microbalance (QCM). Further, the activity coefficients of ions in thin film BCEs were quantified experimentally and these values matched predictions from Manning's theory of counterion condensation if the average distance between fixed charges on the polymer chains were determined accurately. Classical molecular dynamics simulations were also performed to assess counterion condensation and ionic conductivity values. The simulations showed large f c values in the BCE – agreeing with results from GI-SAXS and QCM. Because a holistic approach was adopted, it was uncovered that f c can vary significantly depending on the experimental method and analysis deployed. Interestingly, ionic conductivity measurements of the BCE thin films with aqueous solutions and humidified vapor revealed that solvation is critical for breaking ion pairs, and that the notion of two distinct counterion types, condensed and non-condensed, may not be the most accurate picture despite the utility of Manning's theory for accurately predicting the activity coefficient of ions in polymer electrolytes.